STRATEGI DAKWAH DAN PENDIDIKAN NABI MUHAMMAD SAW : TELAAH KITAB ASAALIIBU AL-RASUL FI AL-DAKWAH WA AL-TARBIYYAH - Nurmaidah, Nurmaidah (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Abstract This article aims to examine the missionary and educational strategies of the Prophet Muhammad SAW in the book Asaaliibu al-Rasul fi al-Dakwah wa al-Tarbiyyah by Shaykh Yusuf Khathir Hassan al-Shuury. Library research is the method of choice in the preparation of this paper, using a literature review approach, namely conducting an in-depth critical study of various literature strategies and methods of da'wah and Islamic education. The book Asaaliibu al-Rasul fi al-Dakwah wa al-Tarbiyyah by Shaykh Yusif Khathir Hasin al-Shuury is the primary reference in studying Islamic da'wah and education strategies. The researcher found three important things related to the prophet's da'wah and education strategy in the book: First: the nature and characteristics of the prophet as an educator consisting of eight characteristics (namely: compassion, patience, intelligence, humility, forgiving, personality integrity, love of profession ) Second, the strategy of the prophet Muhammad SAW in preaching (such as giving gifts and loving each other, correspondence strategies, giving gifts and praise to competent students), Third, the strategy of the prophet in education (direct education/lectures and practice, motivating students, active learning with strategies question and answer, instill a soul bond between educators and students, pay attention to the physical and psychological development of students, instill ukhuwah)